(3GdJYLjR aj GNJUGQ GdhLjRs - (3YHO GdQMje Hf eMeO Hf eMeO Hf jhfS GdehUdjs; (3GdZRGdj , MLI GdESdGe CHh MGeO eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj, MLI GdGSdGe GdZRGdj,J (B505 (3g` s ((3YeQ Hf UGdM Hf MHjH GdLjdi s)
(3ChdgG (B:s
(3CMeO Gddg GdPi Ndb GdEfSGf hYdeg GdHjGf hHYO aNjQ GdcdGe eG bd hOd hdeG cGf cJGH GdhLjR GdPi Cdag GdZRGdi s
(3BNQgG (B:s
(3hGdhdGA ehbha Ef CjSQ hGdGGfbSe bGd GdeDda QVi Gddg Yfg gPG BNQ eG GNJUQJg ef cJGH GdhLjR ddEeGe MLI GdESdGe eMeO GdZRGdi hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3aQZ GdeDda ef JCdjag SfI (B640s
(3fSNJ ai MjGI GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
Keywords: (3Gdabg GdTGaYjs